Analisis Pemberdayaan Kelompok Tani Sejati Bersatu Desa Sejati dalam Perspektif Ekonomi Islam - Anam, Syaiful; Nurdiana, Titin; Ani, Ani; Aziz, Abd. (IQTISODINA, 2025)
This research aims to understand the empowerment of farmer groups in Sejati Village, Camplong District, Sampang Regency from the perspective of Islamic economics. This study is a qualitative descriptive analysis. The research was conducted in Bunut hamlet, Sejati Village, Camplong District, Sampang Regency. The subjects of this study are the Sejati Bersatu farmer group in Sejati Village. The informants for this research include Mr. Muhammad as the head of the Sejati Bersatu farmer group, farmers, and the community of Bunut Hamlet. Data collection was done using methods of observation, interviews, and documentation. Tancehe results of the study indicate that the management of tobacco and chili in Sejati Village, Camplong District, Sampang Regency is in accordance with the perspective of Islamic economics In accordance with the perspective of Islamic economics which includes the principle of monotheism, the principle of maslahah, the principle of mutual assistance, and the principle of working and productivity.